Ready for Takeoff China's Advancing Aerospace Industry - Cliff, Roger (RAND Corporation, 2011)
An assessment of China's aerospace manufacturing capabilities and how China's participation in commercial markets and supply chains contributes to their improvement. It examines China's aviation and space manufacturing capabilities, government efforts to encourage foreign participation, transfers of foreign technology to China, the extent to which U.S. and foreign aerospace firms depend on supplies from China, and their implications for U.S. security interests.